Meningsskapande kommunikation mellan förskollärare och barn vid skapande aktiviteter i förskoleklass - Ahlskog-Björkman, Eva; Furu, Ann-Christin (Nordisk Tidskrift för Allmän Didaktik, 2018)
The aim of this article is to explore communication between early childhood education teachers and children and it´s implications for children´s meaning making during activities in arts and aesthetics in pre-primary settings. Focus is directed towards the communicative approaches of the teachers. The research material consists of video-observations of ten teachers in pre-primary settings. Analysis and interpretation are conducted through a narrative approach. The main findings are expressed in three narratives: 1) The teacher who creates a relationship with the child, 2) The teacher who confirms the initiative of the child, and 3) The teacher who makes meaning making possible. However, the study also reveals that there are considerable variations in the communicative approaches among teachers. This implies unequal premises for children´s meaning making. Based upon the study´s findings, we discuss the importance of an increased awareness among teachers of the importance of communication with respect to children´s meaning making. We also argue that there is a need to highlight communicative skills as a vital part of teacher professionalism.